2013
DOI: 10.1002/adsc.201300568
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a Cytidine 5′‐Monophosphate‐Sialic Acid Synthetase for Improved Tolerance to Functional Sialic Acids

Abstract: Sialic acid-containing glycoconjugates at the cell surface are of high importance in carbohydrate-mediated recognition phenomena in physiological and pathological events, as well as in bacterial or viral infection. A key step in the enzymatic synthesis of natural sialoconjugates and functional synthetic analogues is the activation of sialic acids to cytidine 5'-monophosphate (CMP)-sialic acid intermediates catalyzed by CMP-sialic acid synthetase (CSS). Based on our recently developed aligned protein model of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…However,w en oted that isolated product yields were somewhat lower than anticipatedw hen compared to the complementaryr eactions using the P. leiognathi 2,6SiaT, [19,20] particularly when using only stoichiometric quantitieso fCTP.F or example, upon transfer of the parent Neu5Acalimiting maximum yield of 84 %r esulted for the labelled GM3, whereas the corresponding a2,6-sialylated trisaccharide had been obtained in 93 %y ield. [20] Likewise, the synthesis of unlabeled GM3 trisaccharide from lactose by 2,3SiaT pph catalysis proceeded with an incomplete yield of 86 %o nly.T his indicated that the 2,3-sialyltransfer was sufferingf rom ah ydrolytic uncoupling that was partially causing an unproductive consumptiono ft he limiting CTP quantity.I ndeed, many other 2,3SiaT and 2,6SiaTenzymes from the GT80 familyh ave been shown to display multifunctionality:B esides the desired sialyltransfer activity (A), promiscuous activitiess uch as CMP-Neu5Ac hydrolase (B;s ialyltransfer to water or phosphodiester hydrolysis) and sialidase (C,h ydrolytic cleavage of sialoside linkages) have been recorded (Scheme 2). [21,[24][25][26][27][28][29] Reversibility of sialyltransfer (A)w as recognized as the cause of ap urported trans-sialidase activity,w hich arises from transientC MP-Neu5Ac formation.…”
Section: Substrate Scope Of Native 23siat Pphmentioning
confidence: 88%
See 2 more Smart Citations
“…However,w en oted that isolated product yields were somewhat lower than anticipatedw hen compared to the complementaryr eactions using the P. leiognathi 2,6SiaT, [19,20] particularly when using only stoichiometric quantitieso fCTP.F or example, upon transfer of the parent Neu5Acalimiting maximum yield of 84 %r esulted for the labelled GM3, whereas the corresponding a2,6-sialylated trisaccharide had been obtained in 93 %y ield. [20] Likewise, the synthesis of unlabeled GM3 trisaccharide from lactose by 2,3SiaT pph catalysis proceeded with an incomplete yield of 86 %o nly.T his indicated that the 2,3-sialyltransfer was sufferingf rom ah ydrolytic uncoupling that was partially causing an unproductive consumptiono ft he limiting CTP quantity.I ndeed, many other 2,3SiaT and 2,6SiaTenzymes from the GT80 familyh ave been shown to display multifunctionality:B esides the desired sialyltransfer activity (A), promiscuous activitiess uch as CMP-Neu5Ac hydrolase (B;s ialyltransfer to water or phosphodiester hydrolysis) and sialidase (C,h ydrolytic cleavage of sialoside linkages) have been recorded (Scheme 2). [21,[24][25][26][27][28][29] Reversibility of sialyltransfer (A)w as recognized as the cause of ap urported trans-sialidase activity,w hich arises from transientC MP-Neu5Ac formation.…”
Section: Substrate Scope Of Native 23siat Pphmentioning
confidence: 88%
“…For synthetic studies, the purified 2,3SiaT pph was studied for its transfer activity with at est set of three natural (N-acetylneuraminic acid, 1, N-glycoloyl-neuraminic acid, 2,a nd KDN, 3) and three new-to-nature sialic acid derivatives (4-6,S cheme 1) that were availablef rom previouss tudies. [19,20] Sialic acids were activatedi ns itu by incubation with CSS from Neisseria meningitidis [23] in the presence of cytidinet riphosphate( CTP). Transfer to af luorophore-labeled lactoside 7 [19] was then monitored by HPLC, which showed the smooth conversion of all sialic acid compounds with generation of the expected labelled GM3 (Neu5Aca2-3Galb1-4Glc)t risaccharide 8 and the correspondinga nalogues 9-13 (Scheme 1).…”
Section: Substrate Scope Of Native 23siat Pphmentioning
confidence: 99%
See 1 more Smart Citation
“…A necessary step in such syntheses is to convert the sialic acid to its CMP derivative. Fortunately, N. meningitidis CMP‐sialic acid synthetase133 has broad substrate specificity toward the 5‐position of sialic acids2830 compared to the same enzyme from other species (Figure 9). 134 Fessner and co‐workers reported a simple colorimetric assay for the quantification of CMP‐sialic acid synthetase activity based on the pH change due to the proton released upon nucleotide activation of sialic acids.…”
Section: Syntheses With Modified Sialosidesmentioning
confidence: 99%
“…[84] Recently, the CMP sialic acid synthetase from Neisseria meningitidis has been engineered by site-specific saturation mutagenesis at positions 192/193 to generate mutants with improved catalytic efficiency relative to wild-type CMP sialic acid synthetase for the conversion of sterically demanding N-acyl-modified sialic acid analogues. [85] 3.8. 1.4.4 Tandem Reactions Employing Threonine-Dependent Aldolases Glycine-dependent aldolases catalyze the reversible aldol reaction of glycine with an aldehyde acceptor.…”
mentioning
confidence: 99%